A Phenomenological Exploration of Adoptive Parent Experiences of Support During the Adoption Process. Issue 3 (3rd July 2022) - Shelton, Deena; Bridges, Corinne Wehby
Abstract: Children who age out of foster care face adjustments and mental health issues at higher rates than their peers, but those who are adopted have the opportunity to heal from previous trauma and experience better outcomes. To create healthy family systems for adopted children, adoptive parents need support and guidance as they personally adjust and help their children adjust to a new family system. Previous research has emphasized child identifiers rather than parent influence in efforts to understand adoption success and failure. In this transcendental phenomenological study, adoptive parents provided their lived experiences of support during the adoption process. The results were analyzed using the descriptive phenomenological psychological method and the results were framed using an adapted version of Bronfenbrenner's ecological model. The results offered experiences of support at all 4 levels of the ecological model and provided a framework to use for future research to understand the influences of the sources of support and a guideline for agencies and counselors to use when serving adoptive families. The results can aid in the proactive development of training and support services for adoptive families and provide information for professionals by offering insight into the nontraditional structure of adoptive families.